2018
DOI: 10.3390/su10030795
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Co-Additives (Biochar and FGD Gypsum) on Ammonia Volatilization during the Composting of Livestock Waste

Abstract: The effectiveness of co-additives for improving livestock waste composting (reduction of air pollution and conservation of nutrients) was investigated. Biochar and Flue gas desulphurization gypsum (FGD gypsum) were used to supplement the composting of a mixture of slaughter waste, swine slurry, and sawdust. Different compositions of additives (0% or 5% each, 10% biochar or FGD gypsum) were tested in triplicate on the laboratory scale. In addition, the effects of two different aeration schemes (continuous and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…The measurement protocol was designed to investigate the short-term performance of the additive (T4 and T7) and whether potential washout effects occurred after two weeks when no further additive was applied (T26). The time interval for this study is in line with other works on emissions from manure [25,28].…”
Section: Emission Measurementssupporting
confidence: 71%
See 2 more Smart Citations
“…The measurement protocol was designed to investigate the short-term performance of the additive (T4 and T7) and whether potential washout effects occurred after two weeks when no further additive was applied (T26). The time interval for this study is in line with other works on emissions from manure [25,28].…”
Section: Emission Measurementssupporting
confidence: 71%
“…However, the addition of gypsum has a great capacity to prevent N loss from manure and reduce odor since it reduces NH 3 volatilization during the composting process [27]. NH 3 volatilization reduction has also been confirmed by other authors such as Febrisiantosa et al, Li et al,and Yang et al [24,25,28]. Yang, et al [25] found that phosphogypsum reduced CH 4 and NH 3 emissions from poultry manure composting whilst, on the other hand, tended to increase emissions of N 2 O.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…After inducing strong acidification of manure with sulphuric acid, Petersen et al observed a reduction of CH 4 and NH 3 emissions from cattle slurry [18]. Forms of gypsum as an additive to mitigate emissions from manure have also been tested in numerous studies [19][20][21][22]. The addition of gypsum has shown a reduction in NH 3 emissions during the storage and composting phases of manure, but the results on GHG have not been as clear.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies highlighted fertilizers' role as an additive in composting process to reduce nitrogen loss [37,38]. Few studies focused on the addition of fertilizers in composting process of increasing fertilizer utilization efficiency.…”
Section: Introductionmentioning
confidence: 99%